PERTIMBANGAN HAKIM DALAM PENJATUHAN PIDANA KEKERASAN SEKSUAL KDRT DALAM PUTUSAN NOMOR 1/PID.SUS/2023/PN. PLJ - Muhammad Hauzan Aufa; Itok Dwi Kurniawan (Sebelas Maret University, 2026)
This article aims to determine whether the judge's considerations in imposing a sentence for domestic violence involving sexual assault in Verdict Number 1/Pid.Sus/2023/PN Plj comply with the provisions of Article 183 of the Indonesian Criminal Procedure Code (KUHAP). This article employs normative legal research, with legal materials sourced from primary and secondary legal materials. Primary legal materials include Law Number 8 of 1981 on Criminal Procedure (KUHAP), Law Number 48 of 2009 on Judicial Power, Law Number 23 of 2004 on the Elimination of Domestic Violence, and Verdict Number 1/Pid.Sus/2023/PN Plj. Secondary legal materials consist of legal reference books, legal dictionaries, legal journals, and academic works by legal experts. The legal materials were collected through literature review, and the analysis was conducted using a deductive syllogism method. The research findings indicate that the judge's considerations in Verdict Number 1/Pid.Sus/2023/PN Plj have fulfilled the provisions of Article 183 of KUHAP by taking into account more than two valid pieces of evidence and the judge's conviction, resulting in a verdict that reflects justice and legal certainty.